2019
DOI: 10.1142/s0217751x19501732
|View full text |Cite
|
Sign up to set email alerts
|

X(3872) as virtual companion pole of the charm–anticharm state χc1(2P)

Abstract: We study the spectral function of the axial-vector charmonium state χc1(2P ) coupled to DD * mesons, by employing a quantum field theoretical approach: a pronounced enhancement close to the D 0 D * 0 threshold, to be identified with the X(3872), emerges. In the complex plane we find two poles: a pole for the broad seed state χc1(2P ), and -in the easiest scenario-a virtual pole for the X(3872). Thus, our approach describes both the seed state and the dynamically generated X(3872) simultaneously. In particular,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 92 publications
1
14
0
Order By: Relevance
“…The theoretical basis of this work is that the Xð3872Þ state automatically emerges in the extended Friedrichs scheme and can be expressed as the combination of the cc components and the continuum components such as DD Ã , in which the DD Ã component is dominant [19]. This picture has proved successful in obtaining the mass and width and the isospin-breaking effects of the Xð3872Þ decays [25], and another calculation with the similar spirit also indicates the reasonability of this scheme [26]. This approach can be extended to discuss the decays to χ cJ π 0 processes by considering one of the final states as being a P-wave state.…”
mentioning
confidence: 70%
“…The theoretical basis of this work is that the Xð3872Þ state automatically emerges in the extended Friedrichs scheme and can be expressed as the combination of the cc components and the continuum components such as DD Ã , in which the DD Ã component is dominant [19]. This picture has proved successful in obtaining the mass and width and the isospin-breaking effects of the Xð3872Þ decays [25], and another calculation with the similar spirit also indicates the reasonability of this scheme [26]. This approach can be extended to discuss the decays to χ cJ π 0 processes by considering one of the final states as being a P-wave state.…”
mentioning
confidence: 70%
“…From recent experience in studying the exotic heavy quarkonium-like states like X (3872), it is also demonstrated that by coupling the QCD fundamental qq states with the continuum, not only can the fundamental state itself be modified from the potential model predictions, but also new states can be dynamically generated. This idea was successfully used in explaining the generation of the X (3872) [3,4,[21][22][23][24][25][26]. Actually, this kind of idea has already been widely used in studying the charmonium state [1] and the low lying scalar mesons [27][28][29][30] with some successes.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of this is the X(3872) system. Previous works have focused on the single-channel phase shift [14,79]. Our study here suggests that analyzing the structure of det S may yield a better understanding for characterizing the density of states.…”
Section: Going Furthermentioning
confidence: 72%